2008
DOI: 10.4314/sajas.v37i1.4024
|View full text |Cite
|
Sign up to set email alerts
|

Partial replacement of fish and soyabean meal protein in mirror carp (<i>Cyprinus carpio</i>) diets by protein in hazelnut meal

Abstract: An 80-day feeding trial was conducted as two experiments to evaluate the effects of replacement of fish meal (FM) and soyabean meal (SBM) protein with hazelnut meal (HM) protein in the diets of mirror carp (Cyprinus carpio) fingerlings. Growth parameters and body composition were measured in fingerlings cultured under laboratory conditions in a recirculation system aquarium at 26 ± 0.3 °C. In Experiment I four isonitrogenous, isoenergetic diets were formulated by replacing 0, 25, 35 and 45% of protein from FM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 28 publications
(23 reference statements)
4
19
1
2
Order By: Relevance
“…Similarly, Emre et al (2008b) stated that increasing levels of HM did not affect the PER (1.57-1.64) in sea bass. Ergun et al (2008) confirmed that PER (1.82-2.24) of turbot worsened when the HM rate in the feed came up to 30 %; Büyükçapar and Kamalak (2007) confirmed that PER (1.7-2.1) of carp declined when the HM rate rose to 45 %. In these studies, PER is expected to decline with the increase in HM rate.…”
Section: Discussionsupporting
confidence: 56%
“…Similarly, Emre et al (2008b) stated that increasing levels of HM did not affect the PER (1.57-1.64) in sea bass. Ergun et al (2008) confirmed that PER (1.82-2.24) of turbot worsened when the HM rate in the feed came up to 30 %; Büyükçapar and Kamalak (2007) confirmed that PER (1.7-2.1) of carp declined when the HM rate rose to 45 %. In these studies, PER is expected to decline with the increase in HM rate.…”
Section: Discussionsupporting
confidence: 56%
“…Ullah,(1982) reported that heat treatment will affect the nutritional value of legumes through destruction or inactivation of present factors as well as some impairment in the protein value, because over heating may result in damaging the protein quality by lowering digestibility (denaturation) and causing the loss of sulphur amino acids. According to the report of Buyukcapar and Kamalak, (2007) (2001) reported that watermelon seeds are rich in growth and health promoting nutrients which might be the reason for good nutrient utilization and survival rate attained in this feeding trial, in addition the present study revealed that the proximate analysis of the carcass fish fed the experimental diets were affected in terms of crude protein and fat content by the hydrothermally processed watermelon seed meal. Both the crude protein and lipid content of the initial fish carcass were lower compared with carcass of fish fed the trial diets at the end of experiment.…”
Section: Resultsmentioning
confidence: 68%
“…However, total replacement of soybean meal with hazelnut meal resulted in significantly lower FCR when compared to the other experimental diets (P<0.05). The altered feed efficiency in fish fed the diet with high levels of hazelnut meal has also been reported by Buyukcapar and Kamalak (2007) who evaluated the effects of replacement of fish meal and soybean meal proteins with hazelnut meal protein in the diets of mirror carp fingerlings. They suggested that hazelnut meal could be incorporated into the diet at 35% and 40%, however, dietary inclusion of HNM above these levels caused reduction in feed utilization.…”
Section: Controlmentioning
confidence: 94%
“…Results obtained from this investigation revealed that hazelnut meal could be incorporated into diets formulated for rainbow trout at up to 30% by total replacement of soybean meal in grow-out feed. Only a few studies have reported that hazelnut meal could partially replace fish meal or soybean meal without detrimental effects on growth performance in European sea bass (Emre et al, 2008), carp (Buyukcapar andKamalak, 2007) and rainbow trout (Bilgin et al, 2007). Trout of all groups in this investigation almost tripled their body weight and no significant difference (P>0.05) was revealed in final weight or specific growth rate between treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation